Utility and Validity of Authentic Assessments and Conventional Tests for International Early Childhood Intervention Purposes: Evidence from U.S. National Social Validity Research - Lee, Deborah D.; Bagnato, Stephen J.; Frontczak, Kristie Pretti (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
The reported U.S. incidence of delay/disability in young children, and thus need for services, is far higher than those currently receiving early intervention supports and services [1]. Government representatives and policymakers in the U.S. have concluded that traditional tests fail to capture sufficient numbers of young children who must access early intervention supports at a critical life moment [2], even though state regulations often mandate their use. The early intervention field regards authentic assessments as a more effective alternative. However, few U.S. studies have been conducted to compare and validate the use of either conventional tests or authentic assessments for early intervention purposes. National social validity research in the United States by Bagnato et al. [3,4] revealed that authentic assessments fulfill the qualities/needs of the early childhood intervention field better than conventional tests. However, no national studies had been conducted to examine the qualities and patterns of use for authentic and conventional measures among interdisciplinary professionals. Based on an expanded national internet survey in the current follow-up research, we compared the qualities/patterns of use among professionals for both types of measures in the early childhood intervention field. Overall, median ratings indicate that the top authentic assessments are more valid/useful than the most popular conventional tests to accomplish most early intervention purposes. Based on the results, we share the implications as “practice-based research evidence” to guide international policymakers, professionals, and parents to advocate, choose, and use “best measures for best practices.”